AVALIAÇÃO DO NÍVEL DE MATURIDADE DE PROJETO ATRAVÉS DO PROJECT DESIGN RATING INDEX (PDRI) INCLUINDO A GESTÃO DO DESEMPENHO - Machado, Mauricio Ataide; Andery, Paulo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present work aims presenting the partial results of a research project focusing the development of a conceptual framework as well as a design risk evaluation tool in order to decrease the risks of the design process of real estate projects, embracing the NBR 15.575:2013 requisites. Using the Design Science Research method, an adaptation of the Project Definition Rating Index (PDRI) to be applied in the evaluation of definition level of the design process, including NBR 15.575:2013 requisites. The tool structure and the results of its implementation in a Real Estate Project are outlined. The results point out that the tool seems to be an interesting resource to control, critical analysis and validation of the design process. The research project contribution is significant, since presents a new tool to design risk evaluation including performance-based concepts, applied regarding NBR 15.575:2013.